Antibiotic Resistance, Biofilm Formation and Detection of mexA/mexB Efflux-Pump Genes Among Clinical Isolates of Pseudomonas aeruginosa in a Tertiary Care Hospital, Nepal - Bhandari, Sirjana; Adhikari, Sanjib; Karki, Deepa; Chand, Arun Bahadur; Sapkota, Sanjeep; Dhungel, Binod; Banjara, Megha Raj; Joshi, Prakash; Lekhak, Binod; Rijal, Komal Raj (Frontiers in Tropical Diseases, 2022)
Efflux-pump system and biofilm formation are two important mechanisms Pseudomonas aeruginosa deploys to escape the effects of antibiotics. The current study was undertaken from September 2019 to March 2020 at a tertiary-care hospital in Kathmandu in order to ascertain the burden of P. aeruginosa in clinical specimens, examine their biofilm-forming ability and determine their antibiotic susceptibility pattern along with the possession of two efflux-pump genes-mexA and mexB. Altogether 2820 clinical specimens were collected aseptically from the patients attending the hospital and processed according to standard microbiological procedures. Identification of P. aeruginosa was done by Gram stain microscopy and an array of biochemical tests. All the P. aeruginosa isolates were subjected to in vitro antibiotic susceptibility testing and their biofilm-forming ability was also examined. Presence of mexA and mexB efflux-pump genes was analyzed by Polymerase Chain Reaction (PCR) using specific primers. Out of 603 culture positive isolates, 31 (5.14%) were found to be P. aeruginosa, of which 55% were multi-drug resistant (MDR). Out of 13 commonly used antibiotics tested by Kirby-Bauer disc diffusion method, greatest resistance was shown against piperacillin-tazobactam 15 (48.4%) and ceftazidime 15 (48.4%), and least against meropenem 6 (19.4%) and ofloxacin 5 (16.2%). Of all 17 MDR isolates subjected to biofilm detection, strong biofilm formation was exhibited by 11 (65%) and 14 (82%) isolates with microtiter plate method and tube method respectively. Out of 17 isolates tested, 12 (70.6%) isolates possessed mexA and mexB genes indicating the presence of active efflux-pump system. Higher number of the isolates recovered from sputum 7 (58.3%) and pus 5 (41.7%) possessed mexA/mexB genes while the genes were not detected at all in the isolates recovered from the urine (p<0.05). This study assessed no significant association between biofilm production and multi-drug resistance (p>0.05). Adoption of stern measures by the concerned authorities to curb the incidence of multi-drug resistant and biofilm-forming isolates is recommended to prevent their dissemination in the hospital settings.